SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN PROGRAM STUDI DENGAN METODE SAW DAN AHP - Marbun, Erikson; Hansun, Seng (Prodi Teknik Informatika FIK Universitas Muslim Indonesia, 2019)
Admission to Multimedia Nusantara University (UMN) is divided into academic paths, scholarships and regular tests. The benchmarks used to accept prospective students through the academic track still see five academic grades with a minimum value of 70. There are cases where the minimum grade decreases depending on the KKM (Minimum Completeness Criteria) from the school of the prospective student. The process of changing majors at UMN can be done by going to the Student Support division and undergoing a series of tests depending on the chosen study program. The Student Support Faculty of Engineering and Informatics (FTI) does not have enough data to carry out specific tests. Based on these two problems, a decision support system ‘FTI Recommendation’ was built using the AHP and SAW methods. AHP method is the basis for evaluating prospective students, while the SAW method is for alternative ranking. and the expert reference value as a substitute for the old benchmark, which is 70 or in accordance with KKM from the prospective student's school. The decision support system built produces a satisfaction level of 77.22%.